2017
DOI: 10.1038/srep42100
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Galaxea fascicularis and its endosymbiont Symbiodinium reveals chronic eutrophication tolerance pathways and metabolic mutualism between partners

Abstract: In the South China Sea, coastal eutrophication in the Beibu Gulf has seriously threatened reef habitats by subjecting corals to chronic physiological stress. To determine how coral holobionts may tolerate such conditions, we examined the transcriptomes of healthy colonies of the galaxy coral Galaxea fascicularis and its endosymbiont Symbiodinium from two reef sites experiencing pristine or eutrophied nutrient regimes. We identified 236 and 205 genes that were differentially expressed in eutrophied hosts and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 71 publications
3
8
1
Order By: Relevance
“…These host-specific assemblies represented 26 693–37 894 isogroups (∼genes) with an average length of 1492–1894 bp and an N50 of 1984–2480 (Table 1 ). Mean GC content of host-specific assemblies was 42% (Table 1 ), which is consistent with other anthozoan transcriptomes where Symbiodinium reads have been effectively filtered [ 16 ]. Protein coverage exceeded 0.75 for 37–41% of contigs (Table 1 ).…”
Section: Data Descriptionsupporting
confidence: 81%
See 1 more Smart Citation
“…These host-specific assemblies represented 26 693–37 894 isogroups (∼genes) with an average length of 1492–1894 bp and an N50 of 1984–2480 (Table 1 ). Mean GC content of host-specific assemblies was 42% (Table 1 ), which is consistent with other anthozoan transcriptomes where Symbiodinium reads have been effectively filtered [ 16 ]. Protein coverage exceeded 0.75 for 37–41% of contigs (Table 1 ).…”
Section: Data Descriptionsupporting
confidence: 81%
“…Such information is critical for understanding the adaptive capacity of these ecologically important organisms, particularly in an era of global climate change [ 5 ]. Transcriptomic and/or genomic resources are currently available for 23 scleractinian species representing 14 genera and 11 families [ 1 , 4 , 6 16 ]. We assembled the transcriptomes of 3 scleractinian coral species: the congeners Galaxea astreata, G. acrhelia , and Goniopora columna .…”
Section: Data Descriptionmentioning
confidence: 99%
“…Transcriptome analysis revealed that the blue coral lacks enzymes for key steps in amino acid metabolic pathways and probably relies on its symbionts for amino acids that it is unable to produce. This is similar to what has been shown in A. digitifera , P. australiensis , and G. fascicularis 20 , 21 , 44 . It should be noted, however, that the inability to detect representatives for certain enzymes involved in metabolic pathways may not necessarily indicate their absence from the coral or symbiont genome.…”
Section: Discussionsupporting
confidence: 90%
“…The balance of nutrients is also important, with elevated nitrogen in combination with low phosphorous contributing to coral starvation (D’Angelo & Wiedenmann, 2014). Corals exposed to high nutrients show an upregulation of antioxidant genes indicative of an oxidative stress response (Rosic et al, 2011), as well as genes associated with cell apoptosis and innate immunity (Lin et al, 2016). Despite their immense filtering capabilities, which should increase their exposure to contaminants in the water column, sponges seem comparatively less affected by high nutrient levels.…”
Section: Introductionmentioning
confidence: 99%
“…Individual genes from each GO term/module are detailed in Appendix S1 [Colour figure can be viewed at wileyonlinelibrary.com] in innate immunity have also been identified in corals(DeSalvo, Sunagawa, Voolstra, & Medina, 2010) and sponges(Guzman & Conaco, 2016) in response to increased temperature, as well as in oil-contaminated corals(DeLeo et al, 2018). Most notable, however, is a similar change in gene expression of immunity-related factors in Galaxea fascicularis from eutrophic environments(Lin et al, 2016). Several genes upregulated in G. fascicularis in response to coastal eutrophication were also upregulated in this study, includ-ing Ras-related proteins, apoptosis regulators, tumour necrosis factor receptor proteins, and NF-kappaB signalling (Appendix S1; Lin et al, 2016).…”
mentioning
confidence: 99%